Survey on Mental Toughness and Self-Confidence among Athletes Indonesian National Sports Committee (KONI) of Bekasi City - Dinda Lestari; Dani Nur Riyadi; Aridhotul Haqiyah (Universitas Negeri Semarang, 2025)
This study aims to determine the level of mental toughness and self-confidence in athletes among athletes of the Indonesian National Sports Committee (KONI) Bekasi City in preparation for the qualifying round of the West Java Provincial Sports Week (PORPROV XV) 2025. This study used a quantitative approach involving 140 athletes consisting of pre-teen, teen, and adult categories. Data were obtained through the Sport Mental Toughness Questionnaire (SMTQ) consisting of 14 valid items to measure mental toughness, and a self-confidence questionnaire consisting of 15 valid items. The results showed that in the self-confidence dimension of mental toughness, 140 athletes (100.00%) were classified as high, while 0 athletes (0.00%) were classified as low. In the control dimension, 109 athletes (77.86%) were classified as high, while 31 athletes (22.14%) were classified as low. In the consistency dimension, 131 athletes (93.57%) were classified as high, and 9 athletes (6.43%) were classified as low. Meanwhile, in terms of self-confidence, the indicators showed high categories for optimism (136 athletes, 97.14%), rationality (128 athletes, 91.43%), responsibility (120 athletes, 85.71%), belief in self-ability (104 athletes, 74.29%), and objectivity (80 athletes, 57.14%). As for the low category, the objectivity indicator recorded the highest number (60 athletes, 42.86%), followed by belief in self-ability (36 athletes, 25.17%), responsibility (20 athletes, 14.29%), rationality (12 athletes, 8.57%), and optimism (4 athletes, 2.86%). Overall, all dimensions of mental toughness and self-confidence of the athletes showed a high category, seen from the dominance of the high category in all dimensions measured. This finding indicates that the athletes have good psychological readiness in facing PORPROV XV 2025.